Risk Factors of Post-Partum Depression Among Pregnant Women Attending Primary Health Centers, Mazandaran Province, Iran - Abdollahy, Fatemeh (2011)
Post-partum depression (PPD) is the most common psychological complication of childbirth. Disagreement about the causes of PPD is considerable and currently its etiology is still not fully understood. The aim of this study is to determine the contribution of demographic, sociological, psychological, obstetric and gynecological, cultural and hormone-related risk factors to developing PPD in pregnant women in Mazandaran province, Iran. This is the first ever study of its kind in the country. In this prospective cohort study, 2,279 eligible pregnant women 16 to 45 years of age in their third trimester who attended Primary Health Centers were screened for depression using the Iranian version of Edinburgh Postnatal Depression Scale (EPDS). Of those, 1801 pregnant mothers were found to be free from depression and were followed up 2, 8 and 12 weeks post-partum. The potential risk factors were assessed using 15 standardardized questionnaires. Data were analyzed using Chi-square and simple and multiple logistic regression. Out of 2,279 participants, 478 (21.0%) of those had EPDS score >12 during third trimester of pregnancy. Among 1,801 pregnant mothers who did not have depression during third trimester pregnancy, the cumulative incidence rates of depression occurring in post-partum period were 6.9% (120/1,739), 4.6% (69/1,509) and 4.8% (65/1,357) at 2, 8 and 12 weeks post-partum, respectively. In the multiple logistic regression model, the factors predictive of PPD during the twelve weeks after birth after excluding mothers who were depressed in third trimester of pregnancy were a) depression during the first and second trimester of pregnancy (OR= 2.55, 95% CI=1.59-4.1), b) having a psychiatric disorder in pregnancy based on General Health Questionnaire (GHQ) (OR= 1.08, 95% CI=1.06-1.11), c) gestational diabetes (OR=2.93, 95% CI=1.46-5.88), d) recurrent urinary infection during pregnancy (OR=2.25, 95% CI=1.44-3.52), e) unwanted pregnancy (OR= 2.5, 95% CI= 1.69-3.7), and f) low household income (OR=3.57, 95% CI=1.49-8.5). On the other hand, the risk of post-partum depression was decreased for mothers with elevated age (OR=0.88, 95% CI= 0.84-0.92) and for mothers who reported high self efficacy about mothering based on Parental Expectation Survey (OR=0.7, 95% CI= 0.62-0.78). The findings of this study indicated that a high incidence of post-partum depression was identified in Iranian women, making PPD one of the major public health problems. These findings indicate that several domains of risk factors including demographic, psychological, sociological and obstetric factors put mothers at risk for post-partum depression. Antenatal depressive symptoms were shown to be a key antenatal risk factor for postnatal depression. Culture element was not a risk factor for developing PPD in this traditional society. Key Words: Post-partum depression, risk factors, longitudinal, cohort, Iran